Meningkatkan Motivasi Belajar Matematika melalui Pendekatan Kontekstual di MIN 3 Pringsewu - Kemala, Rizqa Arini; Romlah, Romlah; Afifah, Roifatul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Learning motivation is a crucial factor in determining students' success in understanding mathematical concepts. However, many elementary school students struggle with mathematics due to a lack of active engagement in the learning process. This study aims to enhance students' motivation in learning mathematics through the implementation of a contextual approach using the Classroom Action Research (CAR) method. The subjects of this study were fourth and fifth-grade students at MIN 3 Pringsewu. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included observation, interviews, and student motivation questionnaires. The results showed that implementing a contextual approach significantly increased students' motivation. In the first cycle, student participation increased by 45%, while in the second cycle, the increase reached 75%. Key contributing factors included the use of relevant contexts in learning, active student involvement in discussions, and the implementation of more engaging learning strategies. Thus, this study concludes that a contextual approach can be an effective strategy for enhancing students' motivation in learning mathematics in madrasahs.